PERIPHERAL VENOUS HYPERTENSION AFTER THE CREATION OF ARTERIOVENOUS FISTULA FOR HAEMODIALYSIS - Bachleda, Petr; Kojecky, Zdenek; Utikal, Petr; Drac, Petr; Herman, Jiri; Zadrazil, Josef (Biomedical papers, 2004)
The function of an arteriovenous (av) fistula for haemodialysis may be complicated by manifestation of peripheral venous hypertension, which results from the arterial blood flow through the venous system into the periphery of the upper extremity. Its development is most typically caused by a proximal forearm av-fistula, as, in addition to the desirable arterialisation of the subcutaneous venous system of the arm, arterialisation of the venous system of the forearm and the hand may occur and possibly promote the development of venous hypertension, which may in the extreme result in gangrene of the fingers. Awareness of these problems as well as of the necessity of their surgical solution is essential for doctors dealing with haemodialysis.
Keywords: Arteriovenous fi stula for haemodialysis/Peripheral venous hypertension